2022
DOI: 10.1186/s41100-022-00424-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of antibacterial nanomaterial-induced anaphylactoid reaction for indwelling catheters

Abstract: Background To prevent tunnel infection of indwelling catheters, impregnation with antiseptics or antibiotics is effective. However, 13 patients using chlorhexidine–silver sulfadiazine-impregnated catheters experienced serious anaphylactic shock in Japan. Thus, it is necessary to select a suitable evaluation method for allergic reactions and develop a novel antibacterial coating material that does not cause anaphylactic reaction. Methods Two types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…49 In our earlier research, Zn-HAp nanomaterials with 9% [Zn/(Zn + Ca) × 100] 15 were applied in the anaphylactoid reaction assays using HMC-1 cells. 26 In this study, the Zn ion content in Zn-HAp was increased to 13.5% (the Zn(15)-HAp) which was almost the maximum value of Zn ion-substitution in HAp crystalline lattice formed without ZnO contamination during the synthesis process. 15 Based on this result, it was thought that Zn(15)-HAp nanoparticles are poor at inducing an allergic-like reactions in vitro.
Figure 5.Histamine amounts released from HMC-1 cells.
…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…49 In our earlier research, Zn-HAp nanomaterials with 9% [Zn/(Zn + Ca) × 100] 15 were applied in the anaphylactoid reaction assays using HMC-1 cells. 26 In this study, the Zn ion content in Zn-HAp was increased to 13.5% (the Zn(15)-HAp) which was almost the maximum value of Zn ion-substitution in HAp crystalline lattice formed without ZnO contamination during the synthesis process. 15 Based on this result, it was thought that Zn(15)-HAp nanoparticles are poor at inducing an allergic-like reactions in vitro.
Figure 5.Histamine amounts released from HMC-1 cells.
…”
Section: Resultsmentioning
confidence: 56%
“…Prior to the clinical estimation of anaphylaxis incidence in the implantation of antisepsis-impregnated catheters, 10 in vitro pre-assays of anaphylactoid reactions to antibacterial materials are valuable. Histamine release detection tests involving HMC-1 cells as anaphylactoid reaction assays 26 were conducted by the addition of Zn-HAp nanoparticles (Figure 5). The amount of histamine released from HMC-1 cells after addition of Zn(15)-HAp nanoparticles was not statistically different to that of the negative control (cells alone) and nHAp, but very much lower than that of CHG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indwelling catheters are left in place after insertion, and urine is drained into a collection bag; a water-filled balloon holds the catheter in place within the bladder . This latter type is also known as the Foley catheter, which was invented in 1929 by Frederic Foley. , For both types of catheters, several studies have compared the performance of uncoated versus coated catheters. The most common choice is a hydrophilic polymer coating that becomes slippery when wet. Clinical studies have shown that the use of hydrophilic catheters significantly reduces the incidence of CAUTIs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 23 For both types of catheters, several studies have compared the performance of uncoated versus coated catheters. 24 29 The most common choice is a hydrophilic polymer coating that becomes slippery when wet. Clinical studies have shown that the use of hydrophilic catheters significantly reduces the incidence of CAUTIs.…”
Section: Introductionmentioning
confidence: 99%